DRILLED SHAFT FOUNDATION DESIGN OF PASSENGER TERMINAL & TRAIN STATION BUILDING ADI SOEMARMO INTERNATIONAL AIRPORT IN BOYOLALI - Zain, Azmi
In general, A building consist of two different part, the 1st is the upper structure and the 2nd is the sub-structure. The upper structure where the function of the building held, play a role as the transfer agent to all of the load that subjected to the building, while the sub-structure had a function to support and bear the load that transferred from the upper structure, based on the capacity of the soil below. Remember the importance of it’s role, the sub-structure must designed to be able bear the load, and transfer it to the soil. Beside of it, the sub-structure that hold the position of the building, didn’t allowed to have a deformation degree that goes beyond the deformation limit. This final task is discuss about the drilled shaft foundation design of passenger terminal & train station building in Adi Soemarmo international ariport, boyolali. the work stage of this drilled shaft foundation design are, 1st, interpret the soil data based on the field & laboratory test results. 2nd, run the structure analysis to get the value of load that working on every base joint , this load value will be use to calculate the capability of foundationin the term of support capacity and deformation. After we know the value of load that working on base joint, the pile configuration in a single pile cap will be determine based on the allowable support capacity and deformation degree. This drilled shaft foundation design are calculated by manual method and software application such L-Pile, GROUP, PCA-Column, & Microsoft Office Excel. Output that resulted by this drilled shaft foundation design are dimention, pile configuration, and reinforcement rebar needed in every pile cap type.